The role of the AVAPS ventilation mode combined with TCM monitoring in weaning patients with AECOPD - Nianci Wang; Haidong Qin; Lei Bao (Scientific Reports)
Abstract To explore the role of AVAPS combined with TCM monitoring in the weaning of patients with AECOPD. In this study, 100 patients with AECOPD were included, who were divided into the AVAPS group and the S/T group after weaning. The respiration-related parameters were compared between the two groups at the time of weaning and after 1 h and 12 h of noninvasive ventilation. The correlations between PtcCO2 and PaCO2 and the differences in each parameter were compared. The predictive value of PtcCO2 variability after 1 h and 12 h of noninvasive respiratory support for the 48-h reintubation rate were analysed. Logistic regression analysis was performed to explore the risk factors affecting the 48-h reintubation rate of AECOPD patients. After 1 h and 12 h of treatment with different ventilation modes, the variations in the respiration-related parameters in the AVAPS group were all significantly greater than those in the S/T group (P < 0.05). In the AVAPS group, the incidence of 48-hour reintubation was lower, the time to reintubation was longer, and length of hospital and ICU stays were shorter (P < 0.05). The ROC curve revealed that PtcCO2 variability− 2, the ROX index− 2 and their combination had predictive value for the 48-h reintubation rate of AECOPD patients. The logistic regression revealed that after 12 h of noninvasive support, a PtcCO2 variability ≥ − 5.8% with a ROX index ≤ 9.6 was independent risk factors affecting the 48 h reintubation rate in weaning patients with AECOPD (OR = 2.815; P < 0.05). For patients with AECOPD, the AVAPS ventilation mode combined with PtcCO2 monitoring can significantly improve respiratory physiological parameters and reduce the 48 h reintubation rate. After 12 h of noninvasive support, a PtcCO2 variability ≥ − 5.8% with a ROX index ≤ 9.6 is considered as a independent risk factor for reintubation 48 h after weaning.